Problematic Internet Use and Cyberbullying: Does Executive Function Moderate the Association? - Emma Yuniarrahmah (Psychology Program, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2026)
The advancement of information and communication technology, along with increased internet use via social media, has contributed to a shift from traditional bullying to cyberbullying. Cyberbullying frequently occurs among adolescents who regularly access the internet and social media through smartphones or computers. Excessive internet use may disrupt daily functioning and contribute to maladaptive online behavior. This study examined whether executive function moderates the association between problematic internet use and cyberbullying tendencies among adolescents. A quantitative cross-sectional survey was conducted among 316 adolescents aged 15–20 years in South Kalimantan, Indonesia (M = 17.61). Participants were selected using purposive sampling. Data were collected using the Cyberbullying Tendency Scale, the Problematic Internet Use Questionnaire Short-Form (PIUQ-SF-6), and the Executive Skills Questionnaire-Revised (ESQ-R). The data were analyzed using Hayes’ PROCESS macro. The results showed that executive function moderated the association between problematic internet use and cyberbullying tendencies. However, executive function was not significantly associated with cyberbullying tendencies, and problematic internet use was not significantly associated with cyberbullying tendencies. Executive function serves as a key variable that can either strengthen or weaken the influence of problematic internet use on cyberbullying tendencies, despite not being directly associated with either construct. These results suggest that cyberbullying prevention strategies may be more effective when focused on enhancing cognitive regulation and digital behavior management, particularly among adolescents at risk for problematic internet use.